Estudo das alterações histológicas da mucosa de corneto nasal inferior em pacientes com e sem rinite alérgica. - ZAUPA, Michelle Campos (2023)
The allergic or non-allergic rhinitis is an inflammatory disease of the upper airways with considerable impact on quality of life and worldwide prevalence ranging from 10 to 20%. The inflammation observed in this pathology leads to structural changes in upper airway mucosa, but the mechanism still unclear. The Initiative Allergic Rhinitis and its Impact on Asthma (2008) postulated the theory of united airways disease due to extensive inter relationships between rhinitis and asthma, because this diseases would be a pathologic continuum. With the development of this theory, doubts were originated if the histological changes of the upper and lower airways are similar. Studies have shown changes in upper airway mucosa, for example metaplasia, epithelial erosion, basement membrane, thickening, intense inflammatory infiltrate and glandular hyperplasia, besides other findings on electron microscopy, all in less that occurred in the lower airways of patients with asthma. Objective: To describe and evaluate histological findings of lower nasal turbinate mucosa of patients with and without allergic rhinitis. Methodology: a prospective, longitudinal descriptive study was submitted and approved by the Ethics Committee in Research of the Federal University of Pará. The study was conducted at the University Hospital Bettina Ferro de Souza, with patients undergoing turbinectomy surgery from March 2010 to June 2011. Clinical data were obtained through the research protocol (Appendix A) completed by the medical examiner. The inferior nasal turbinate samples were sent for histopathological examination performed by a single pathologist and studied microscopically. Results: Samples were obtained from 14 patients, ten men and four women ranging in age from 17 to 56 years. Three (21.4%) patients had non-allergic rhinitis (prick test negative) and 11 (78.6%) diagnosed with allergic rhinitis (prick test positive). The main symptoms reported were sneezing with 78.6% followed by nasal obstruction with 71.4%. The analysis of the lamina showed the following findings: 100% had respiratory epithelium and lymphocytic infiltration, glandular hyperplasia 85.7%, 64.3% of the basement membrane thickening, eosinophilia 50% and 28.6% erosion of the epithelium. Conclusion: The population consisted mostly of men with a mean age of 35 years. Among patients prick test negative to most are female. The patients had positive prick test present secretory-like symptoms and the patients with a negative result complained of nasal obstruction. All patients had inflammatory infiltration mainly of the mild type. Among patients prick test positive were marked the presence of eosinophilia, but it was not possible to relate this with the severity of symptoms.